A study of zinc borne waste water treatment with dispersion supported liquid membrane. (21st September 2016) - Lu, Shibao; Pei, Liang
Abstract: This paper based on a theoretical study of the supported liquid membrane separation technology, explores the appropriate liquid membrane separation system, makes a study on the Pb (II) transmission behavior in the PC-88A-kerosene-HCl dispersion supported liquid membrane system and reviews influence of the feed liquid pH value, volume ratio between the membrane liquid and analytic agent, HCI concentration during analytic phase and initial Pb (II) transmission concentration. The results show that the migration of Pb (II) is well completed for 190 min with the migration rate being up to 95% on the premise that the feed liquid pH is equal to 6.0, Pb (II) initial concentration of 3.0 × 10 −3 mol/L, HCl concentration during the stripped and dispersed phase is 4.0 mol/L, volume ratio between the stripped liquid and organic phase is 40:160 and that of the conventional supported liquid membrane is only 72.4%. The dispersion supported liquid membrane is characterized by higher transmission efficiency, stable membrane system and long membrane service life. The procedure has provided accurate results with zinc borne waste water treatment.